Update on Phase I Studies in Advanced Pancreatic Adenocarcinoma. Hunting in Darkness? - Strimpakos, Alexios S; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Over the last twenty years, there is a limited number of effective cytotoxic or biological agents that managed to get approval in advanced pancreatic ductal adenocarcinoma. Despite numerous trials, investments in translational research and generally in health care, the survival of pancreatic cancer patients has improved by a few only months. This disappointing reality necessitates a better understanding of the pathogenesis of this disease and the identification of targetable alterations which might lead to development of more effective drugs or better combinations. At the 2013 Annual Meeting of the American Society of Clinical Oncology, few novel agents and new therapeutic concepts, tested in phase I studies in advanced pancreatic ductal adenocarcinoma, were presented. The first notable phase I study referred to the combination of chemotherapy with local delivery of silencing RNA against the K-ras mutation G12D, in advanced pancreatic ductal adenocarcinoma, which was well tolerated and promising (Abstract #4037). The second one referred to a combination of gemcitabine with pegylated recombinant human hyaluronidase (PEGPH20), an inhibitor of hyaluronan which as a matrix glycosaminoglycan is believed to play role in the reduced drug delivery to cancer (Abstract #4010). The other notable abstract was related to an early phase study which tested the safety and toxicity of arctigenin, a traditional herbal agent found in Arctium lappa Linné, administered as an oral formulation (GMS-01) in pancreatic ductal adenocarcinoma patient resistant to standard chemotherapy (Abstract #2559). The aforementioned early phase studies open new therapeutic approaches which deserve further testing in advanced pancreatic cancer. Image: The biennial plant Arctium lappa Linné. <!–[endif] –>